2018
DOI: 10.3390/foods7110190
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of pH, NaCl, and the Deacidifying Yeasts Debaryomyces hansenii and Kluyveromyces marxianus on the Production of Pigments by the Cheese-Ripening Bacteria Arthrobacter arilaitensis

Abstract: Arthrobacter arilaitensis is a food-related bacterial species under investigation for its involvement in the coloration of surface-ripened cheeses. Presently, information about this species in association with the development of appropriate cheese coloration is still lacking. This study was performed in order to investigate—with the use of spectrocolorimetry—the influence of pH, NaCl, and deacidifying yeasts on the pigmentation of Arthrobacter arilaitensis biofilms. Three types of cheese-based (curd) solid med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…Fontina PDO is characterized by a reddish sticky surface, naturally formed by the microflora of the surrounding environment which colonizes the rind during the ripening period [ 3 ]. A minor diversity of coloration of smear cheese rind may depend on the interactions between microbial species, pH, NaCl concentration, and temperature [ 16 , 17 ]. By contrast, the rind of Fontal cheese is usually coated with a protective film (paraffin, wax, or varnish) to prevent the growth of surface microflora and colored with red-brown pigments to obtain a standardized external appearance of the cheese regardless maturity.…”
Section: Resultsmentioning
confidence: 99%
“…Fontina PDO is characterized by a reddish sticky surface, naturally formed by the microflora of the surrounding environment which colonizes the rind during the ripening period [ 3 ]. A minor diversity of coloration of smear cheese rind may depend on the interactions between microbial species, pH, NaCl concentration, and temperature [ 16 , 17 ]. By contrast, the rind of Fontal cheese is usually coated with a protective film (paraffin, wax, or varnish) to prevent the growth of surface microflora and colored with red-brown pigments to obtain a standardized external appearance of the cheese regardless maturity.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the yellow pigments, which were characterized as a group of C50 carotenoids consisting of eight forms, but mainly decaprenoxanthin, G. arilaitensis has recently been reported to synthesize red pigment(s) [17][18][19]. In our previous study [19], a strain of G. arilaitensis, Po102, evidently developed pink/red-brown color suffusing inside inoculated cheese-based (curd) solid media. After a tentative determination, the results showed that the pink pigments excreted by this strain were water-soluble and fluoresced under UV light.…”
Section: Introductionmentioning
confidence: 93%
“…Arthrobacter arilaitensis (presently named Glutamicibacter arilaitensis-to be up to date, G. arilaitensis will be used throughout this article) is one of the important bacterial strains responsible for the pigmentation of cheese rinds due to its presence at different stages of the ripening process, principally at the middle and late stages [15,16]. Besides the yellow pigments, which were characterized as a group of C50 carotenoids consisting of eight forms, but mainly decaprenoxanthin, G. arilaitensis has recently been reported to synthesize red pigment(s) [17][18][19]. In our previous study [19], a strain of G. arilaitensis, Po102, evidently developed pink/red-brown color suffusing inside inoculated cheese-based (curd) solid media.…”
Section: Introductionmentioning
confidence: 99%
“…The color of the rind of smear-ripened cheeses is the objective of the research paper by Sutthiwong et al [8]. They report that the yellow colonies of Arthrobacter arilaitensis (now Glutamicibacter arilaitensis ) greatly contribute to the pigmentation of this type of rind.…”
Section: Articles Of the Special Issuementioning
confidence: 99%